Prospects of honey in fighting against COVID-19: pharmacological insights and therapeutic promises - Hossain, Khandkar Shaharina (Heliyon, 2020)
Honey and its compounds are drawing attention as an effective natural therapy because of its ability to attenuate acute inflammation through enhancing immune response. Several studies have proved its potential healing capability against numerous chronic diseases/conditions, including pulmonary disorders, cardiac disorders, diabetes, hypertension, autophagy dysfunction, bacterial, and fungal infections. More importantly, honey has proved its virucidal effect on several enveloped viruses such as HIV, influenza virus, herpes simplex, and varicella-zoster virus. Honey may be beneficial for patients with COVID-19 which is caused by an enveloped virus SARS-CoV-2 by boosting the host immune system, improving comorbid conditions, and antiviral activities. Moreover, a clinical trial of honey on COVID-19 patients is currently undergoing. In this review, we have tried to summarize the potential benefits of honey and its ingredients in the context of antimicrobial activities, some chronic diseases, and the host immune system. Thus, we have attempted to establish a relationship with honey for the treatment of COVID-19. This review will be helpful to reconsider the insights into the possible potential therapeutic effects of honey in the context of the COVID-19 pandemic. However, the effects of honey on SARS-CoV-2 replication and/or host immune system need to be further investigated by in vitro and in vivo studies.